AMI observations of Lynds dark nebulae: further evidence for anomalous cm-wave emission - Scaife, A.; Hurley-Walker, Natasha; Green, D.; Davies, M.; Franzen, Thomas; Grainge, K.; Hobson, M.; Lasenby, A.; Pooley, G.; Rodriguez-Gonzalvez, C.; Saunders, R.; Scott, P.; et al. (Oxford University Press, 2009)
Observations at 14.2 to 17.9 GHz made with the Arcminute Microkelvin Imager (AMI) SmallArray towards 14 Lynds dark nebulae with a resolution of ˜2 arcmin are reported. Thesesources are selected from the Submillimetre Common-User Bolometre Array (SCUBA) observationsof Visser, Richer & Chandler as small angular diameter clouds well matched to thesynthesized beam of the AMI Small Array. Comparison of the AMI observations with radioobservations at lower frequencies with matched uv-plane coverage is made, in order to searchfor any anomalous excess emission which can be attributed to spinning dust. Possible emissionfrom spinning dust is identified as a source within a 2-arcmin radius of the SCUBA positionof the Lynds dark nebula, exhibiting an excess with respect to lower frequency radio emission.We find five sources which show a possible spinning dust component in their spectra. Thesesources have rising spectral indices in the frequency range 14.2–17.9 GHz with a17.914.2=-0.7±0.7 to -2.9 ± 0.4, where S ? ?-a. Of these five one has already been reported, L1111, we reportone new definite detection, L675 (16s), and three new probable detections (L944, L1103and L1246). The relative certainty of these detections is assessed on the basis of three criteria:the extent of the emission, the coincidence of the emission with the SCUBA position and thelikelihood of alternative explanations for the excess. Extended microwave emission makes thelikelihood of the anomalous emission arising as a consequence of a radio counterpart to aprotostar or a protoplanetary disc unlikely. We use a 2-arcmin radius in order to be consistentwith the IRAS identifications of dark nebulae, and our third criterion is used in the case ofL1103 where a high flux density at 850 µm relative to the far-infrared data suggests a morecomplicated emission spectrum.